Uniaxial Tension of a Filament-wound Composite Tube at Low Temperature - Szabó, Gyula; Váradi, Károly (Acta Technica Jaurinensis, 2018)
The aim of this article is to model mechanical behavior of a filament-wound, rubber-based composite tube subjected to uniaxial tension at low temperature by test experiments and FE simulations. Uniaxial tensile tests at sub-zero temperature (-40 °C) have been carried out on standard test specimens and on hose pieces. furthermore, a uniaxial tensile test has been performed on a hose piece at room temperature as a reference experiment. Reinforcement layers of the composite tube are modeled as transversely isotropic, whereas elastomer liners are described by 2 parameter Mooney-Rivlin hyperelastic material model. Temperature-dependence of elastic constants of composite layers is attributed to the temperature-dependence of rubber, so uniaxial tensile tests on standard test specimens needed to be carried out for determining material properties of rubber at sub-zero temperature (-40°C). Force-displacement results of FE models and experiments of standard test specimen and hose piece show good agreement. Likewise, force-displacement curves of reference experiment (carried out at room temperature) and its related FE simulation are in good agreement with each other. Slope of force-displacement curves of hose piece at -40 °C is nearly 3.4 times the slope of force-displacement curves of hose piece at room temperature.